An Increase of the Mineral Contents of Barley Grain by Genotype, Planting Time and Seed Size - Kandemir, Nejdet; Tuzen, Mustafa; Sari, Hayati; Mendil, Durali (Asian Journal of Chemistry, 2016)
In this study, cultivars, planting time and seed size were examined as potential factors to improve mineral composition of barley grain. Ten barley genotypes of different origins were studied. Fall and spring plantings were compared using five cultivars. Four seed size groups of two cultivars were also studied. There were considerable variations for most minerals among barley cultivars and hence, choice of appropriate cultivars may result in better mineral compositions. H. spontaneum, a wild relative of cultivated barley, contained high amounts of Ca, Fe and Mn minerals. In general, fall planted barley had higher mineral content than spring planted barley. Seed size did not affected mineral contents of the seed except copper where smaller seeds had higher copper.